Ascending notions of Personhood in the Bhāgavata Purāṇa Dedicated to Professor Klaus K. Klostermaier on the occasion of his Seventy-fifth Anniversary - Teʾodor, Itamar (Religions of South Asia, 2008)
The paper looks at one of the main themes of the Bhāgavata Purāṇa, which is the theme of ascending notions of Divine Personhood; these sequential notions are arranged in hierarchical order, resembling a ladder. they evoke various emotional states, each more complex and more intense then the previous one, beginning with a state that evokes śānta and culminating in a state that evokes śṛṅgāra.